2021
DOI: 10.1002/ecs2.3775
|View full text |Cite
|
Sign up to set email alerts
|

A riverscape approach reveals downstream propagation of stream thermal responses to riparian thinning at multiple scales

Abstract: A riverscape approach reveals downstream propagation of stream thermal responses to riparian thinning at multiple scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…Streams flowing through forests provide habitat for a diverse array of aquatic organisms [10,11] as well as serve as sources of drinking water for downstream communities [12]. Because headwater streams represent 80-90% of miles of any given river network [13], reducing impacts from forest harvest to headwater streams can have broad implications locally as well as downstream [11,14].…”
Section: Terrestrial Disturbances In Headwaters and The Role Of Ripar...mentioning
confidence: 99%
“…Streams flowing through forests provide habitat for a diverse array of aquatic organisms [10,11] as well as serve as sources of drinking water for downstream communities [12]. Because headwater streams represent 80-90% of miles of any given river network [13], reducing impacts from forest harvest to headwater streams can have broad implications locally as well as downstream [11,14].…”
Section: Terrestrial Disturbances In Headwaters and The Role Of Ripar...mentioning
confidence: 99%
“…Finally, larger catchments would require more extensive harvesting to impact streamflow (Brown et al, 2005; Zhang et al, 2017); therefore, the potential moderating influence of increased streamflow on stream temperature response may not be sufficient if only a small portion of the catchment is harvested. A number of complexities emerge when scaling from small headwater systems to larger stream networks, such as changes in dominant hydrologic and energy exchange processes, as well as interactions between cumulative effects (Bladon et al, 2018; Leach et al, 2021; Roon et al, 2021). Further research is needed to understand stream temperature response to forest disturbance at network scales (Jones, 2010; Steel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These results are also consistent with studies of stream warming following forest harvests (Groom et al, 2011; Moore, Spittlehouse, & Story, 2005). For example, Roon, Dunham, & Torgersen et al, (2021) reported the magnitude of warming and downstream extent of heated water was proportional to the length of stream reach adjacent to harvests. Water temperatures eventually cooled with distance below the harvest units, once the streams were again shaded by riparian vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…We did not estimate how warming varied by pond area, but warming was shown to increase in relation to pond area in other studies (Fuller & Peckarsky, 2011) and remains a topic for future research. Like Roon, Dunham, & Torgersen et al, (2021), however, we expect that the distance over which warmer stream temperatures persisted downstream was related to the magnitude of warming.…”
Section: Downstream Warmingmentioning
confidence: 96%
See 1 more Smart Citation